Extração sustentável e caracterização da pectina obtida do mamão formosa - Guevara, Santos Pedraza (2020)
Papaya (Carica papaya L.), the best-known plant of the caricaceae family, being cultivated in tropical and subtropical countries such as Brazil, is widely consumed in natura when ripe. Part of papaya production is not used due to its appearance, climatic damage, or insects or due to overproduction. The unripe papaya is rich in total dietary fibers and can be used as an alternative source for pectin extraction. The aim of the study was to establish a green protocol for pectin extraction from unripe papaya flour (UPF), comparing conventional acid hydrolysis (CONV) and compressed fluid extraction (CFE) techniques, including Pressurized Hot Water Extraction (PHWE) and Enhanced Solvent Extraction (ESE). First, unripe papaya flour (UPF) was produced to be used as raw material before its physicochemical characterization. For conventional extraction, different operating conditions were evaluated, including the particle size of the raw material, the solid-solvent ratio, and the type of organic acid. The highest pectin yields were achieved with ESE (216±10.8 mg g-1) when CO2+H2O (20:80) + citric acid (5%, 1 mol L-1) was applied (40 MPa/80 ºC/60 min/300–710 μm), similar to that obtained by CONV (202.0±49.5 mg g-1) and PHWE (208.0±9.4 mg g-1) using oxalic acid. UPF pectin presented an average galacturonic acid (GalA) content of 73% (w/w) and degree of esterification (DE) of 57.8%, and it was composed predominantly of galactose, glucose and rhamnose. This pectic substance has been shown to contain two main types of pectic chains: rhamnogalacturonan-I (RG-I, average 58%) proportionally higher than homogalacturonan (HG, average 28%). Both conventional extraction techniques and compressed fluid techniques allowed obtaining high quality pectin with a composition similar to other commercial products, also reinforcing CFE as a sustainable process.